2003
DOI: 10.1093/jat/27.5.313
|View full text |Cite
|
Sign up to set email alerts
|

Foxy, a Designer Tryptamine Hallucinogen*

Abstract: Foxy is slang for 5-methoxy-N,N-diisopropyltryptamine. It has hallucinogenic properties, similar to other tryptamine compounds, and is mildly euphoric. This case report describes a 21-year-old Caucasian man who ingested a pill called Foxy containing an unknown amount of drug. He was observed in hospital for 2 h, during which time he had mild hallucinations and could not move his limbs. A urine sample was collected approximately 4 h after drug ingestion. The patient was then discharged with no follow up assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 12 publications
2
54
1
1
Order By: Relevance
“…5-MEO-DIPT was first synthesized by Shulgin and Carter (1980) and was described as inducing auditory and visual hallucinations in humans lasting 3-6 h. Emergency room reports and recent case studies confirm the auditory and visual hallucinogenic properties of 5-MEO-DIPT and suggest that the drug can also produce tactile hallucinations, agitation, tachycardia, somatic disturbance, cataleptic states, unconsciousness, flashbacks, increased glucose levels, vomiting, rhabdomyolysis, and in at least one case, seizure activity or death (Alatrash et al, 2006;Ikeda et al, 2005;Kiyota, 2004;Meatherall and Sharma, 2003;Muller, 2004;Smolinske et al, 2004;Tanaka et al, 2006;Wilson et al, 2005). From case studies, users have reported administering various amounts of the drug (ie, 10-37.5 mg) via oral or rectal routes of administration (Ikeda et al, 2005;Kiyota, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5-MEO-DIPT was first synthesized by Shulgin and Carter (1980) and was described as inducing auditory and visual hallucinations in humans lasting 3-6 h. Emergency room reports and recent case studies confirm the auditory and visual hallucinogenic properties of 5-MEO-DIPT and suggest that the drug can also produce tactile hallucinations, agitation, tachycardia, somatic disturbance, cataleptic states, unconsciousness, flashbacks, increased glucose levels, vomiting, rhabdomyolysis, and in at least one case, seizure activity or death (Alatrash et al, 2006;Ikeda et al, 2005;Kiyota, 2004;Meatherall and Sharma, 2003;Muller, 2004;Smolinske et al, 2004;Tanaka et al, 2006;Wilson et al, 2005). From case studies, users have reported administering various amounts of the drug (ie, 10-37.5 mg) via oral or rectal routes of administration (Ikeda et al, 2005;Kiyota, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…5-MEO-DIPT, like MDMA, is a 'club drug' popular at raves; because of its association with MDMA and abuse potential, it was classified as Schedule I as of September 2004 (Drug Enforcement Administration (DEA), 2004). The drug has been found to be in use throughout the United States, Canada, Japan, and Europe (Drug Enforcement Administration (DEA), 2004;EMCDDA, 2004;Kiyota, 2004;Meatherall and Sharma, 2003). Interestingly, even before the drug was scheduled in the United States, over 12 000 tablets, 500 capsules, and 6.5 kg of 5-MEO-DIPT were confiscated between 1999(Drug Enforcement Administration (DEA), 2004.…”
Section: Introductionmentioning
confidence: 99%
“…The class of N,N-dialkylated tryptamines has been a constant element of interest within the context of new psychoactive substances (NPS) (Meatherall and Sharma, 2003;Smolinske et al, 2005;Tanaka et al, 2006;Vorce and Sklerov, 2004;Wilson et al, 2005). Another newer tryptamine, 5-methoxy-N,N-diallyltryptamine (5-MeO-DALT), was associated with a fatal poisoning (Elliott and Evans, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Three clinical case reports [2][3][4] and one experimental study [5] have concerned 5-MeO-DIPT intoxication. Meatherall & Sharma [3] reported that 5-MeO-DIPT may cause mild hallucinations and motor disturbances lasting for 3.5 hours, while Wilson et al [4] reported transient tactile hallucinations resolving after 4 hours of observation in an emergency ward. Shulgin & Carter [5] further demonstrated that experimental administration of 5-MeO-DIPT produced effects lasting up to 6.5 hours.…”
Section: Discussionmentioning
confidence: 99%